Monitoring compliance with clinical protocol and therapeutic guidelines for alzheimer’s disease - Forgerini, Marcela [UNESP]; Mastroianni, Patrícia de Carvalho [UNESP] (FapUNIFESP (SciELO), 2020)
Dementia is a chronic neurodegenerative disease and Alzheimer’s disease (AD) is the most prevalent type. Objective: To describe the drug monitoring of patients enrolled in a Clinical Protocol and Therapeutic Guidelines of Alzheimer’s Disease (PCDTDA) in Brazil. Methods: A descriptive study based on interviews conducted in 2017 was performed. Patients diagnosed with Alzheimer’s disease (AD) enrolled on the PCDTDA were included. The variables assessed were age, sex, time since diagnosis, clinical parameters of Mini-Mental State Exam (MMSE) and Clinical Dementia Rating (CDR), drug therapy used and AD drug collection. Results: The drug monitoring of 143 patients was evaluated. Observing the requirements of the screening tests for patient enrolment on the PCDTDA, all patients had scores for at least one MMSE and CDR assessment at protocol admission. None of the patients underwent the first reassessment of the effectiveness of AD drug therapy or the semiannual reassessment. Conclusion: Although PCDTDA provides the best evidence of AD treatment, the data showed failures in the monitoring of the effectiveness of AD drug therapy at dispensing.
Monitoramento do cumprimento do protocolo clínico e diretrizes terapêuticas da doença de alzheimer.
Keywords: Clinical protocols; Dementia; Drug monitoring; Drug safety; Patient safety